Soft computing approach to viewpoint-controlled virtual texture loading - Ma, Jinzhao; Li, Gen; Fang, Zhengfu; Zheng, Jiangbin; Cao, Jun (The Journal of systems and software, 2025)
Textures are a crucial element in computer graphics, essential for creating realistic visual effects. Virtual texture technology plays an important role in achieving large-scale texture loading and real-time rendering of natural terrains. However, existing texture loading methods often face performance bottlenecks on low-power platforms, leading to excessive resource consumption. To address this issue, identifying an effective texture loading strategy becomes particularly important. This study proposes a viewpoint-controlled soft computing approach, specifically the application of fuzzy logic, to optimize the virtual texture loading process. By analyzing user viewpoint behavior and the importance of different regions within an image, our method can intelligently adjust the resolution of textures, thereby reducing hardware resource consumption during the loading process. By introducing soft computing techniques, this paper aims to achieve more efficient large-scale texture rendering, especially in resource-constrained environments. Our research not only provides a new perspective on the development of virtual texture technology but also offers practical solutions for graphics processing on low-power platforms. [Display omitted] •Proposed fuzzy logic-driven texture loading for low-power platforms, prioritizing key parameters via soft computing.